2014
DOI: 10.1063/1.4898581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ferroelectric nanoparticles on ion transport in a liquid crystal

Abstract: A small quantity of BaTiO3 ferroelectric nanoparticles (FNPs) of 50 nm diameter was doped in a nematic liquid crystal (LC), and the free ion concentration was found to be significantly reduced in the LC + FNP hybrid compared to that of the pure LC. The strong electric fields, due to the permanent dipole moment of the FNPs, trapped some mobile ions, reducing the free ion concentration in the LC media. The reduction of free ions was found to have coherent impacts on the LC's conductivity, rotational viscosity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…The analysis of publications shows that a lot of studies with using different types of nanoparticles are already performed. The most promising direction to modify functionalities of LC is ferroelectric nanoparticles [1][2][3][4][5][6][7]. One of the features of these nanoparticles is the presence of a strong local electric field.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of publications shows that a lot of studies with using different types of nanoparticles are already performed. The most promising direction to modify functionalities of LC is ferroelectric nanoparticles [1][2][3][4][5][6][7]. One of the features of these nanoparticles is the presence of a strong local electric field.…”
Section: Introductionmentioning
confidence: 99%
“…%) did not lead to the corresponding decrease of the ion concentration because of the aggregation of nanoparticles. However, at this level of nanoparticle loading, the concentration of ions was still ~1.3 times smaller than that of the pure (non-doped) 5CB [199]. The measured values of the electrical conductivity (at a temperature of 25 °C) were m S / 10 95 .…”
Section: Ferroelectric Nanoparticles In Liquid Crystalsmentioning
confidence: 97%
“…%) [197]. Effect of 3 BaTiO ferroelectric nanoparticles on the ion transport in the nematic liquid crystal 5CB was reported in [199]. By introducing relatively low quantities of 3 BaTiO nanoparticles, the concentration of mobile ions in 5CB was reduced by a factor of ~1.5 (at a concentration of 0.115 wt.…”
Section: Ferroelectric Nanoparticles In Liquid Crystalsmentioning
confidence: 97%
See 1 more Smart Citation
“…carbon nanotubes, silica microbeads, nanoparticles and various collides exhibit remarkable new physical phenomena. Experiments have shown that nanoparticles and ferroelectric nanoparticles can greatly enhance the physical properties of nematic and smectic liquid crystals [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%